Role of three-dimensional printing in periodontal regeneration and repair: Literature review - Meisha Gul; Aysha Arif; Robia Ghafoor (Wolters Kluwer Medknow Publications, 2019)
Three-dimensional (3D) printing is the process of building 3D objects by additive manufacturing approach. It is being used in endodontics, periodontology, maxillofacial surgery, prosthodontics, orthodontics, and restorative dentistry, but our review article is focused on periodontal application. A detailed literature search was done on PubMed/Medline and Google Scholar using various key terms. A total of 45 articles were included in this study. Most of the studies were in vitro, preclinical, case reports, retrospective, and prospective studies. Few clinical trials have also been done. Periodontal applications included education models, scaffolds, socket preservation, and sinus and bone augmentation and guided implant placement. It showed better alveolar ridge preservation, better regenerative capabilities, greater reduction in pocket depth and bony fill, ease of implant placement in complex cases with greater precision and reduced time with improved outcome and an important tool for education and training using simulated models.